Answer:
[tex]y = -7x -13[/tex]
Step-by-step explanation:
Given
Perpendicular to
[tex]7y = x -4[/tex]
Passes through
[tex](-2,1)[/tex]
Required
The equation
First, we calculate the slope of:
[tex]7y = x -4[/tex]
Divide through by 7
[tex]y = \frac{1}{7}x - \frac{4}{7}[/tex]
A linear function is:
[tex]y=mx + c[/tex]
Where;
[tex]m \to slope[/tex]
So:
[tex]m = \frac{1}{7}[/tex]
For the perpendicular line; the slope is:
[tex]m_2 = -\frac{1}{m}[/tex]
So, we have:
[tex]m_2 = -\frac{1}{1/7}[/tex]
[tex]m_2 = -7[/tex]
The equation is:
[tex]y = m(x - x_1) + y_1[/tex]
So, we have:
[tex]y = -7(x - -2) + 1[/tex]
[tex]y = -7(x +2) + 1[/tex]
Open bracket
[tex]y = -7x -14 + 1[/tex]
[tex]y = -7x -13[/tex]